2008
DOI: 10.1007/s12036-008-0035-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetic activity on ionospheric time delay at low latitude

Abstract: The purpose of this work is to investigate the effect of magnetic activity on ionospheric time delay at low latitude Station Bhopal (geom. lat. 23.2 • N, geom. long. 77.6 • E) using dual frequency (1575.42 and 1227.60 MHz) GPS measurements. Data from GSV4004A GPS Ionospheric Scintillation and TEC monitor (GISTM) have been chosen to study these effects. This paper presents the results of ionospheric time delay during quiet and disturbed days for the year 2005. Results show that maximum delay is observed during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…However, more evidences are required as the occurrences of two events namely minor SSW and geomagnetic storms in near-coincident condition complicated the interpretation of observed variability in QTDWs. Our finding is inline with previous studies which among others show that during an ionospheric storm (e.g., Bhattacharya et al, 2008 dissipation of electric currents and which then should lead to a significant decrease in the atom-to-molecule ratio throughout the entire high latitude atmosphere.…”
Section: Amplitude Modulation Of Major Wave Componentssupporting
confidence: 92%
“…However, more evidences are required as the occurrences of two events namely minor SSW and geomagnetic storms in near-coincident condition complicated the interpretation of observed variability in QTDWs. Our finding is inline with previous studies which among others show that during an ionospheric storm (e.g., Bhattacharya et al, 2008 dissipation of electric currents and which then should lead to a significant decrease in the atom-to-molecule ratio throughout the entire high latitude atmosphere.…”
Section: Amplitude Modulation Of Major Wave Componentssupporting
confidence: 92%
“…Strength of anomaly is also correlated with electrojet strength and is maximum during the equinox months (Rastogi and Klobuchar 1990;Rama Rao et al 2006). The ionospheric variability during geomagnetic quiet and disturbed condition is reported by earlier workers (Richmond 1995;Fuller-Rowell et al 1997;Dsagupta et al 2007;Bhattacharya et al 2008; Mukherjee Bhattacharya et al (2008) have studied variation of GPS-derived TEC during geomagnetic quiet and disturbed period at Bhopal, India. They have shown that TEC during disturbed period is found to be higher than TEC during quiet period in the winter season while TEC during quiet period is higher than the TEC during disturbed period in the equinox season.…”
Section: Tec Variation During Geomagnetic Quiet and Disturbed Daysmentioning
confidence: 55%
“…Ionospheric delay is caused by the presence of free electrons in the ionosphere which is the ionized portion of the upper atmosphere. The ionospheric delay is dispersive in nature and depends on the frequency of the signal (Bhattacharya et al, 2008). It can be eliminated by the use of a linear combination of two or multiple frequencies since the GNSS broadcasts at two or more separate frequencies.…”
Section: Introductionmentioning
confidence: 99%